A Two-Component Language for Adaptation: Design, Semantics and Program Analysis - Degano, Pierpaolo; Ferrari, Gian-Luigi; Galletta, Letterio (IEEE transactions on software engineering, 2016)
Adaptive systems are designed to modify their behaviour in response to changes of their operational environment. We propose a two-component language for adaptive programming, within the Context-Oriented Programming paradigm. It has a declarative constituent for programming the context and a functional one for computing. We equip our language with a dynamic formal semantics. Since wrong adaptation could severely compromise the correct behaviour of applications and violate their properties, we also introduce a two-phase verification mechanism. It is based on a type and effect system that type-checks programs and computes, as an effect, a sound approximation of their behaviour. The effect is exploited at load time to mechanically verify that programs correctly adapt themselves to all possible running environments.